Super-Darcy flow behavior in fracture-confined porous media - Shuai Zhang; Qing Ma; Weiqiang Xie; Kai Liu; Yanlin Su; Mingxin Zhao; Zefan Wang; Jinpeng Zhao; Xiaoli Liu (Proceedings of the National Academy of Sciences, 2026)
Particle deposition and migration within fractures can reorganize open void space into heterogeneous fracture-confined porous media (FCPM), yet the macroscopic flow behavior of these emergent systems remains unresolved. Here, Computational Fluid Dynamics–Discrete Element Method (CFD–DEM) simulations were used to resolve particle migration and deposition, whereas a coupled free-flow and seepage-flow model was employed to characterize fluid flow in FCPM. We find that at a fixed Reynolds number, modest particle deposition can lower the overall pressure drop relative to that of the initially open fracture. At high Reynolds numbers, the pressure drops across FCPM not only exceed Darcy’s law predictions (non-Darcy behavior) but, intriguingly, can also fall below them, which is a phenomenon we term super-Darcy behavior. This counterintuitive effect arises from flow exchange between the deposited porous region and the adjacent open region, which modifies eddy formation and growth, thereby broadening the main flow channel. This effect is pronounced when the permeability of the deposited porous region lies from 1 × 10 −12 to 1 × 10 −7 m 2 , identifying a permeability window in which deposition–migration most strongly couples pore-scale structure to fracture-scale hydraulics. This study reveals how particle deposition and transport govern macroscopic flow behavior in fractured channels, offering critical insights for fluid flow control and prediction from microfluidic devices to subsurface energy reservoirs.